Exploration on Improving Practical Teaching Mode through College-Enterprise Cooperation under the Background of "New Engineering" - Yan Cui (Forest Chemicals Review)
Under the background of "New Engineering", the innovation of training mode in Colleges and universities is imperative. Under the trend of multi specialty integration, we should also pay attention to the innovation of specific teaching forms. It is an effective way to promote the reform of teaching practice by making better use of the platform of College-Enterprise Cooperation. We have increased the breadth and depth of College-Enterprise Cooperation, and achieved good results by introducing project-based and engineering teaching forms into enterprises.